2018
DOI: 10.1371/journal.pone.0193490
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of S4 segments and S4-S5 linkers to the low-voltage activation properties of T-type CaV3.3 channels

Abstract: Voltage-gated calcium channels contain four highly conserved transmembrane helices known as S4 segments that exhibit a positively charged residue every third position, and play the role of voltage sensing. Nonetheless, the activation range between high-voltage (HVA) and low-voltage (LVA) activated calcium channels is around 30–40 mV apart, despite the high level of amino acid similarity within their S4 segments. To investigate the contribution of S4 voltage sensors for the low-voltage activation characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Whole-cell Ca 2+ (and Na + ) currents were recorded at room temperature (21–23 °C) with the patch-clamp technique following the methods of Sanchez-Sandoval et al [ 35 ]. External solutions composition was as follows (in mM): for LVA channels, 5 CaCl 2 and 175 TEA-Cl; for HVA channels, 10 BaCl 2 and 152 TEA-Cl; and for sodium channels, 158 NaCl, 2 CaCl 2 , and 2 MgCl 2 .…”
Section: Main Textmentioning
confidence: 99%
“…Whole-cell Ca 2+ (and Na + ) currents were recorded at room temperature (21–23 °C) with the patch-clamp technique following the methods of Sanchez-Sandoval et al [ 35 ]. External solutions composition was as follows (in mM): for LVA channels, 5 CaCl 2 and 175 TEA-Cl; for HVA channels, 10 BaCl 2 and 152 TEA-Cl; and for sodium channels, 158 NaCl, 2 CaCl 2 , and 2 MgCl 2 .…”
Section: Main Textmentioning
confidence: 99%
“…Detailed studies on domain I by the same group pointed out its importance for channel activation and showed that the S5 and S6 region rather than voltage sensing S1-S4 were critical [9]. Swapping of S4 segments between Cav3.3 channels and Ca V 1.2 channels demonstrated that IIS4 and, to a lesser degree IVS4, segments are crucial in determining the negative voltage threshold of Ca V 3.3 channel activation [10]. …”
Section: Introductionmentioning
confidence: 99%